Computerized on-line test system / Roslan Lin - Lin, Roslan (2012)
This project presents a software development that allows lecturers and students to login for the on-line test. To login for the first time, the lecturer must use user ID: admin and password: admin. Lecturers can create and edit tests and test banks, create and edit student accounts, print tests questions and print test scores. The student can take the tests online and have their tests marks for the objective questions just after the test. For the essay questions, the lecturer will check and give their marks later. The marks for the essay and objective questions will add up together before their grade is given. The students' information is held on a database that can be accessed through Graphical User Interface (GUI).The software is developed using Visual Basic 6.0 with Query based on ActiveX Data Object 2.0 Library (ADO), File Transfer Protocol (FTP) and Inet. Database is held on Microsoft Access 97.